Zoos and animal rights : the ethics of keeping animals - Bostock, Stephen St. C., 1940- (London ; New York : Routledge, 1993)
A controversial and timely book which explores the long history of zoos as well as the diverse ethica l and technical issues involved. Anyone concerned with humanity's relationship with other animals will find this an inspiring and rewarding book.
(cont) Why conservation is a moral matter -- Caring for objects -- Different ways of conserving -- Vandalism -- Animals as natural works of art -- Animals as animals -- Why animals merit double respect -- Zoos and conservation -- Conservational captive breeding -- Breeding technology -- Culling -- Reintroduction -- Species selection, valuing and finance -- Supplementary conservational roles -- Science in zoos -- Taxonomy -- General observation and investigation -- Veterinary study -- Genetics -- Behaviour -- Source for anatomical material -- Milieu for scientific activities -- On zoos not being scientific -- Usefulness of science in zoos -- Education in zoos -- Why keep real animals? -- Involvement with animals -- On zoological and other gardens -- On real plants and animals -- Communities or prisons? -- Taking animals from the wild.
Includes bibliographical references (pages 198-213) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Zoo animals; Zoos -- Philosophy; Animal welfare; Animal rights; Animal Rights; Animal Welfare; Animals, Zoo; Ethics; Animaux de jardin zoologique; Jardins zoologiques -- Philosophie; Animaux -- Protection; Animaux -- Droits; NATURE -- Animal Rights; Animal rights; Animal welfare; Zoo animals; Zoos -- Philosophy; Dierentuinen; Rechten van het dier; Ethiek; Animal rights